The role of bank lending in the monetary transmission process of a developing economy: the Malaysian evidence - Kassim, Salina; Abd. Majid, M. Shabri (2008)
This study attempts to provide empirical evidence on the importance of bank loan in channelling monetary policy effects to the real economy. Based on the Malaysian data, the study focuses on a sample period spanning from January 1989 to December 2006. It explores the causal relationships between bank loan and monetary policy variable using two major tests; first, the auto-regressive distributed lag (ARDL) model which is used to examine the long-run relationship among the variables and second, the vector error-correction model (VECM) which is adopted to explore the short- and long-run dynamics between the variables. To further enrich the discussion, the study includes bank deposit so as to compare the importance of bank asset (loan) and liability (deposit) in the monetary transmission process. The results of the study show that both bank loan and deposit play crucial role in the monetary transmission process in the Malaysian case. In particular, bank loan is shown to provide an important nexus from monetary policy to output in the short run, while bank deposit is an important channel of monetary policy in the long run. The relevance of bank loan and deposit in the monetary transmission process implies the importance of ensuring the stability of the banking system as a pre-requisite to effective monetary policy implementation, thus the economic stability in the country.